Ormiański Kościół Apostolski w procesie transformacji ustrojowej w Armenii - Fedorowicz, Krzysztof (My University, 2019)
The Armenian Apostolic Church in the process of system transformation in Armenia. The Armenian Apostolic Church in the process of system transformation in Armenia. The Armenian Apostolic Church has played a very important role in Armenia’s social developments. Due to the Church’ role in the nation’s history, it has become of the most significant institutions in the lives of Armenians. The article is an attempt at showing the role of the Armenian Apostolic Church in the process of system transformation in Armenia. The author indicates its privileged role and the difficulties accompanying acceptance of other denominations in Armenia. Attention is also paid to the Church’s close cooperation with the political elites.
Keywords: Church; Armenia; transformation; Armenians; institutions